Comparison of insect biomass and community structure between fynbos sites of different ages after fire with particular reference to ants, leafhoppers and grasshoppers - Schlettwein, C. H. G.(Carl-Hermann Gustav); National Programme for Environmental SciencesCommittee for Terrestrial EcosystemsFynbos Biome Project (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1984.